Analysis of airspace organization considering air traffic flows - Kondroška, Vaidotas; Stankūnas, Jonas (Transport, 2012)
Aviation is one of the most rapidly developing types of transport playing a crucial role in the modern world. Aviation has a sensitive response to any economic or social changes and painful aviation catastrophes. In spite of increasing the flows of passengers and flights, for certain reasons, the aviation system does not always satisfy the expectations of the airspace users in the sense of efficiency. The effectiveness of air transport operations is determined by both a reduction in the costs of every airspace user and the efficiency of the air traffic management system. Airspace organization performed by the air traffic management system, i.e. its adaptation to the performance of appropriate air navigation services, largely defines the efficiency of these services. Due to various reasons, presently, the area of airspace and airspace management has remained one of the largest and incompletely used aviation resources. Beside other appropriate means, the organization of air traffic management and airspace establishes flight conditions and determines the efficiency of flight trajectories and regularity. A comparison of air traffic management systems of different regions identifies the obstacles that do not allow ensuring the maximum results of flight efficiency in any place. One of the main reasons is the high fragmentation of the specified regions that mostly coincide with the state borders. The above reasons show that in order to efficiently develop aviation, the successful development of that to the extent of one country is not enough. Thus, the best results will only be reached solving the existing problems and intended challenges to the extent of a few countries – up to the extent of the whole region. The aim of research is to define a methodology allowing the organization of regional airspace according to the flows of air traffic and subsequently enabling to solve flight efficiency problems related to air traffic management. For space evaluation, the paper suggests using rectangular grids the application of which makes possible dividing the researched space more easily and exactly. Considering the examples of air traffic management systems demonstrating the best results of efficiency, it can be exactly assumed about the number of possible airspace blocks complying with the flows of flights in the analyzed airspace. In case, a preliminary number of the wanted clusters is known, it is purposeful to apply the method of the cluster analysis of K-means with necessary limitations to the formed building airspace blocks and to determine the optimum version taking into account the analyzed ones. The paper suggests representing points having appropriate weighted coefficients during the stage of clustering rather than using grid cells. The optimization of the obtained airspace blocks is necessary in case the formed blocks do not properly comply with the aims raised. The application of the methodology suggested in the paper enables dividing the airspace of a big territory into airspace blocks according to the flows of flights independent from the air way network, flight intensity and the collocation of the airspace elements of a special purpose. First Published Online: 19 Sep 2012